2013
DOI: 10.2166/hydro.2013.134
|View full text |Cite
|
Sign up to set email alerts
|

Improved annual rainfall-runoff forecasting using PSO–SVM model based on EEMD

Abstract: Rainfall-runoff simulation and prediction in watersheds is one of the most important tasks in water resources management. In this research, an adaptive data analysis methodology, ensemble empirical mode decomposition (EEMD), is presented for decomposing annual rainfall series in a rainfall-runoff model based on a support vector machine (SVM). In addition, the particle swarm optimization (PSO) is used to determine free parameters of SVM. The study data from a large size catchment of the Yellow River in China ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(86 citation statements)
references
References 64 publications
1
84
0
1
Order By: Relevance
“…These results are consistent with those of previous studies dealing with hybrid modeling for rainfall-runoff process [6,47,[99][100][101]. Single MLMs (e.g., ANN, ELM, and LSSVR) represent a natural limitation in terms of nonstationary hydrologic time series modeling even if they can model nonlinear hydrologic time series effectively [102,103].…”
Section: Performance Assessmentsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with those of previous studies dealing with hybrid modeling for rainfall-runoff process [6,47,[99][100][101]. Single MLMs (e.g., ANN, ELM, and LSSVR) represent a natural limitation in terms of nonstationary hydrologic time series modeling even if they can model nonlinear hydrologic time series effectively [102,103].…”
Section: Performance Assessmentsupporting
confidence: 91%
“…It has been reported that these hybrid MLMs, which consists of time series decomposition and sub-time series modeling, were able to achieve better performance compared with the single MLMs. Finally, the hybrid MLMs, combined with more than two methods, have been developed for rainfall-runoff and streamflow modeling including DWT, PSO, and SVMs [45]; DWT, GA, and adaptive neuro-fuzzy inference system (ANFIS) [46]; EEMD, PSO, and SVMs [47]; EEMD, SOM, and linear genetic programming [48]; wavelet transform, singular spectrum, chaotic approach, and SVR [49]; and Hermite-projection pursuit regression, social spider optimization, and least square algorithm [50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PSO algorithm is derived from the migration mechanism of birds during foraging, which has advantages of fast convergence, efficient parallel computing and strong universality which is able to efficiently avoid local optimum [23,24]. Moreover, the iteration velocity of particle is influenced by the sum of current velocity, historical particle value, current global optimal value and random interferences, which avoids local optima to a large extent and improves search coverage and effectiveness.…”
Section: Pso Parameter Calibration Methodsmentioning
confidence: 99%
“…In the late 1980s, research on artificial neural network (ANN) applications advanced after the introduction of backpropagation training algorithms for feedforward ANNs [3]. ANNs, which simulate the biological nervous system and brain activity, have become the preferred forecasting approach in hydrology and hydrometeorology (e.g., [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]). ANNs are advantageous because feedforward networks are universal approximators capable of learning continuous functions with any desired degree of accuracy.…”
Section: Introductionmentioning
confidence: 99%